2011
DOI: 10.1177/0963721411424740
|View full text |Cite
|
Sign up to set email alerts
|

Resilience

Abstract: When adverse life events occur, people often suffer negative consequences for their mental health and well-being. More adversity has been associated with worse outcomes, implying that the absence of life adversity should be optimal. However, some theory and empirical evidence suggest that the experience of facing difficulties can also promote benefits in the form of greater propensity for resilience when dealing with subsequent stressful situations. I review research that demonstrates U-shaped relationships be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
2
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(63 citation statements)
references
References 17 publications
2
58
2
1
Order By: Relevance
“…Repeated exposure to emotionally charged situations across the lifetime may lead to increased expertise in dealing with them (Charles, 2010). Specifically, people are thought to gain practice in regulating their emotions to the extent that life events are experienced and resolved across life (Blanchard-Fields, Mienaltowski, & Seay, 2007; see also Seery, 2011). Moreover, older age has been linked to changes in the motivation to regulate emotions (Carstensen et al, 1999).…”
Section: Age Differences In Emotional Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Repeated exposure to emotionally charged situations across the lifetime may lead to increased expertise in dealing with them (Charles, 2010). Specifically, people are thought to gain practice in regulating their emotions to the extent that life events are experienced and resolved across life (Blanchard-Fields, Mienaltowski, & Seay, 2007; see also Seery, 2011). Moreover, older age has been linked to changes in the motivation to regulate emotions (Carstensen et al, 1999).…”
Section: Age Differences In Emotional Stabilitymentioning
confidence: 99%
“…First, if persons experience fewer stressors overall, they should have more resources available to cope with a single stressor when it does occur. Second, if stressors are more homogenous (i.e., the same or very similar stressors reoccur over time), they should be more predictable and it should be easier to establish adequate coping strategies, resulting in reduced reactivity (for a similar argument regarding the role of practice for emotion regulation, see Charles, 2010, andSeery, 2011). Third, if stressors generally have a lower impact on routines, the affective reaction to stressors should be smaller (Lazarus & Folkman, 1984).…”
Section: Life Context Effects On Emotional Stabilitymentioning
confidence: 99%
“…Collective identity also has the potential to foster positive self-esteem, academic achieve-volume 5(1),  ment, psychological and socio-cultural adjustment, and adaptation to adversities such as discrimination or prejudice, to which minority members are generally more vulnerable. In that sense, collective identity may increase individual self-regulatory and coping skills (Seery, 2011;Umaña-Taylor, Gonzales-Backen, & Guimond, 2009) and attenuate problematic developmental outcomes associated with the risks in environments the adolescent try to fit in (Garcia Coll & Magnusson, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is a tendency to compare majority groups of the host society with immigrant communities, whereas fewer studies take into consideration majority groups in comparison with national minorities, i.e., ethnic groups who live in one country, but are simultaneously ethnic kins of the population of another, often neighboring country. Since collective identity fosters positive and resilient developmental trajectories, it is important to advance our understanding on its distinctive as well as joint contribution as a resource that enhances youth well-being (Russo, Murrough, Han, Charney, & Nestler, 2012;Seery, 2011). Developmental assets such as skills, experiences, relationships, and behaviors that facilitate healthy development and their unfolding among minority youth have been so far relatively understudied (Bialystok, Majumder, & Martin, 2003;García Coll et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…This raises the question of whether the type, magnitude and severity of a violent act may limit possibilities for post-traumatic growth. Research into the relationship between lifetime trauma history and mental health has found an inverted U-shape curve, such that individuals who have experienced very low or very high levels of trauma are less resilient than individuals who have experienced a moderate level of trauma (Seery, 2011). It therefore seems plausible that there might be an upper severity limit for perpetration of violence, beyond which post-traumatic growth is unlikely to occur.…”
Section: Questions For Future Researchmentioning
confidence: 99%